Pendampingan Penggunaan AI dalam Jurnalistik, Melalui Pendekatan Jurnalistik Verifikasi - Faisyal, Faisyal; Haris, Abdul (Oratio Directa (Prodi Ilmu Komunikasi), 2024)
AbstractJournalism is a job that is always in touch with technology. Along with the development of telecommunications technology, journalism has also made changes in the production process, namely using artificial intelligence (AI). Because AI offers various conveniences, but still has a number of weaknesses. It needs to be accompanied by caution when using it, because there is a high risk that if the data presented by AI is inaccurate, information bias can occur. The public consumes wrong news, has the potential to have wrong perceptions and behave wrongly. The presence of verification journalism can reduce the birth of information bias produced by journalists using AI assistance. The principle of verification journalism makes journalists always careful, because in working journalistic verification prioritizes ethics and truth.Keywords: Artificial intelligence, verification journalism, audience perception.